The Role of Self-Directed E-Learning-Based Mental Health Models in Strengthening Mental Health Literacy among Nurses in West Lombok Regency, Indonesia: A Cross-Sectional Study - Sirajunnasihin Sirajunnasihin; Wulandari Dewi Susilawati; Musparlin Halid (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Nurses at Public Health Centers (PHCs) are at the forefront of providing health services, including mental health services. Adequate Mental Health Literacy (MHL) is crucial to enhance their ability to recognize, manage, and support patients with mental health disorders. Improving MHL through an Self-Directed E-Learning (SDE) based learning approach is expected to be an innovative solution to strengthen nurses' competencies. The study aimed to analyze the association between the self-directed e-learning-based mental health model and the strengthening of MHL among nurses at PHC. Methods: The study used a cross-sectional design to analyze the association between exposure to SDE with the strengthening of MHL among nurses at PHC in West Lombok, West Nusa Tenggara, Indonesia, with a sample size of 263. Descriptive analysis was performed to describe the characteristics of the respondents. Chi-square and binary logistic regression tests were performed to determine the association between variables with a significance level of p<0.05 with 95% Confidence Interval (CI) and Adjusted Odds Ratio (AOR) to determine the depth of the association. Results: The results of the study show that most nurses with high SDE exposure have better MHL-work levels than nurses with low SDE exposure. Males have a higher chance of achieving competency improvement than females (AOR=3.046; p=0.004). Participants with a Diploma in Nursing also showed a significant improvement compared to Bachelor of Nursing graduates (AOR=2.208; p=0.042). Work experience of ?5 years had a significant effect (AOR=2.851; p=0.006). A history of work-related MHL training significantly increased the likelihood of competency (AOR=3.575; p=0.001). Higher exposure to SDE, including the number of reflective discussion and practice sessions (AOR=2.333; p=0.029), longer e-learning duration (AOR=3.524; p=0.001), and the number of modules completed (AOR=2.617; p=0.018), and the number of mental disorder patients treated (AOR=3.703; p=0.001) were found to be significantly associated with increased competency. Meanwhile, workload did not show a significant association (p=0.231). Conclusions: The study findings confirm that experience, education, training, and intensity of involvement in the SDE program are important determinants in improving MHL competencies.